Body mass index and prognosis of infective endocarditis - Raquel Frías-García; Patricia Muñoz García; Marina Machado Vilchez; Gregorio Cuerpo Caballero; Raquel Rodríguez-García; M Ángeles Rodríguez-Esteban; M Carmen Fariñas-Álvarez; José M. Miró Meda; Andrea Gutiérrez Villanueva; Guillermo Ojeda-Burgos; Ane Josune Goikoetxea-Agirre; Marina Bernal Palacios; et al. (Infectious Diseases, 2025)

Recent Results on Science and Innovation Related to Electrical Processes of Thunderstorms - Christoph Köhn; Torsten Neubert; Martin Füllekrug; Ute Ebert; Sander Nijdam; Olivier Chanrion; Nikolai Østgaard; Martino Marisaldi; Serge Soula; Joan Montanyà; Francisco Gordillo-Vázquez; Alejandro Luque; et al. (Surveys in Geophysics, 2025)

The Early to Late Cretaceous (Albian–Cenomanian) transition in Putumayo, Colombia: A biostratigraphic and carbon isotope stratigraphic correlation for northwestern South America - Javier Luque; Jonatan Bustos; Manuel Páez-Reyes; Alejandro Beltrán-Triviño; Angie Rodríguez; Alexandra Delgado; Johan M. Sánchez; Julián Caraballo; Mikel A. López-Horgue (Palaeoworld, 2025)

Extracts from Microalgae and Archaea from the Andalusian Coast: A Potential Source of Antiproliferative, Antioxidant, and Preventive Compounds - Cristina Luque; Gloria Perazzoli; Patricia Gómez-Villegas; Javier Vigara; Rosario Martínez; Alejandro García-Beltrán; Jesús M. Porres; Jose Prados; Rosa León; Consolación Melguizo (Journal of Marine Science and Engineering, 2024)
Marine and extreme environments harbor a huge diversity of microorganisms able to produce new bioactive metabolites with beneficial health effects. In this study, ethanol, aqueous, methanol, and acetone extracts and protein hydrolysates were obtained from five different microalgae species and two haloarchaea. An in vitro study of cytotoxicity, migration, angiogenic effect, antioxidant capacity, and modulation of detoxifying enzyme expression was carried out using resistant (HCT-15) and non-resistant (T84) colon cancer tumor lines. Our results showed that the aqueous extract of the microalga Chlorella sorokiniana induced the greatest cytotoxic effect in both cell lines, while the ethanolic extracts of the archaea Haloarcula hispanica and Halobacterium salinarum caused the greatest inhibition on the migratory capacity. Meanwhile, the protein hydrolyzate and the aqueous extract of the microalga Chlorella sorokiniana significantly protected cells against hydrogen peroxide damage. Moreover, the aqueous extracts of Haloarcula hispanica and Halobacterium salinarum resulted in inducing the greatest increase in the activity of the detoxifying enzymes enzyme quinone oxidoreductase and glutathione S-transferase. These preliminary results suggest that aqueous extracts of some microalgae and haloarchaea may be promising candidates for an adjuvant therapy against colorectal cancer. However, additional research is required to identify the active principles and elucidate the mechanisms of action involved.

NEOTROPICAL FRESHWATER FISHES : A dataset of occurrence and abundance of freshwater fishes in the Neotropics - Lívia Helena Tonella; Renata Ruaro; Vanessa Salete Daga; Diego Azevedo Zoccal Garcia; Oscar Barroso Vitorino; Tatiana Lobato‐de Magalhães; Roberto Esser dos Reis; Fabio Di Dario; Ana Cristina Petry; Michael Maia Mincarone; Luciano Fogaça de Assis Montag; Paulo Santos Pompeu; et al. (Ecology, 2023)
The Neotropical region hosts 4225 freshwater fish species, ranking first among the world's most diverse regions for freshwater fishes. Our NEOTROPICAL FRESHWATER FISHES data set is the first to produce a large‐scale Neotropical freshwater fish inventory, covering the entire Neotropical region from Mexico and the Caribbean in the north to the southern limits in Argentina, Paraguay, Chile, and Uruguay. We compiled 185,787 distribution records, with unique georeferenced coordinates, for the 4225 species, represented by occurrence and abundance data. The number of species for the most numerous orders are as follows: Characiformes (1289), Siluriformes (1384), Cichliformes (354), Cyprinodontiformes (245), and Gymnotiformes (135). The most recorded species was the characid Astyanax fasciatus (4696 records). We registered 116,802 distribution records for native species, compared to 1802 distribution records for nonnative species. The main aim of the NEOTROPICAL FRESHWATER FISHES data set was to make these occurrence and abundance data accessible for international researchers to develop ecological and macroecological studies, from local to regional scales, with focal fish species, families, or orders. We anticipate that the NEOTROPICAL FRESHWATER FISHES data set will be valuable for studies on a wide range of ecological processes, such as trophic cascades, fishery pressure, the effects of habitat loss and fragmentation, and the impacts of species invasion and climate change. There are no copyright restrictions on the data, and please cite this data paper when using the data in publications.

Microwave-assisted MOF@biomass layered nanomaterials: Characterization and applications in wastewater treatment - Kevin Jhon Fernández-Andrade; Alex Ariel Fernández-Andrade; Luis Ángel Zambrano-Intriago; Luis Ernesto Arteaga-Perez; Serguei Alejandro-Martin; Ricardo José Baquerizo-Crespo; Rafael Luque; Joan Manuel Rodríguez-Díaz (Chemosphere, 2023)

Coastal Flooding in the Balearic Islands During the Twenty-First Century Caused by Sea-Level Rise and Extreme Events - Pau Luque; Lluís Gómez-Pujol; Marta Marcos; Alejandro Orfila (Frontiers in Marine Science, 2021)
Sea-level rise induces a permanent loss of land with widespread ecological and economic impacts, most evident in urban and densely populated areas. Potential coastline retreat combined with waves and storm surges will result in more severe damages for coastal zones, especially over insular systems. In this paper, we quantify the effects of sea-level rise in terms of potential coastal flooding and potential beach erosion, along the coasts of the Balearic Islands (Western Mediterranean Sea), during the twenty-first century. We map projected flooded areas under two climate-change-driven mean sea-level rise scenarios (RCP4.5 and RCP8.5), together with the impact of an extreme event defined by the 100-year return level of joint storm surges and waves. We quantify shoreline retreat of sandy beaches forced by the sea-level rise (scenarios RCP4.5 and RCP8.5) and the continuous action of storm surges and waves (modeled by synthetic time series). We estimate touristic recreational services decrease of sandy beaches caused by the obtained shoreline retreat, in monetary terms. According to our calculations, permanent flooding by the end of our century will extend 7.8–27.7 km 2 under the RCP4.5 scenario (mean sea-level rise between 32 and 80 cm by 2100), and up to 10.9–36.5 km 2 under RCP8.5 (mean sea-level rise between 46 and 103 cm by 2100). Some beaches will lose more than 50% of their surface by the end of the century: 20–50% of them under RCP4.5 scenario and 25–60% under RCP8.5 one. Loss of touristic recreational services could represent a gross domestic product (GDP) loss up to 7.2% with respect to the 2019 GDP.

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

The Involvement of Phytophthora Root Rot and Drought Stress in Holm Oak Decline: from Ecophysiology to Microbiome Influence - Francisco José Ruiz-Gómez; Alejandro Pérez-de-Luque; Rafael María Navarro-Cerrillo (Current Forestry Reports, 2019)

Histopathology of the infection on resistant and susceptible lentil accessions by two contrasting pathotypes of Fusarium oxysporum f.sp. lentis - Hamid Reza Pouralibaba; Alejandro Pérez-de-Luque; Diego Rubiales (European Journal of Plant Pathology, 2017)

Design, Characterization, and In Vitro Evaluation of Antifungal Polymeric Films - Daniel A. Real; María V. Martinez; Agustín Frattini; Marina Soazo; Alicia G. Luque; Marisa S. Biasoli; Claudio J. Salomon; Alejandro C. Olivieri; Darío Leonardi (AAPS PharmSciTech, 2013)

Single and combined influence of ACE and ACTN3 genotypes on muscle phenotypes in octogenarians - Nuria Garatachea; Carmen Fiuza-Luces; Gema Torres-Luque; Thomas Yvert; Catalina Santiago; Félix Gómez-Gallego; Jonatan R. Ruiz; Alejandro Lucia (European Journal of Applied Physiology, 2012)

Screening techniques and sources of resistance against parasitic weeds in grain legumes - Diego Rubiales; Alejandro Pérez-de-Luque; Mónica Fernández-Aparico; Josefina C. Sillero; Belén Román; Mohamed Kharrat; Shaban Khalil; Daniel M. Joel; Charlie Riches (Euphytica, 2006)